2023
DOI: 10.3390/en16052338
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Cavities: Configurative Systematic Review

Abstract: This study is a systematic review of research on heat transfer analysis in cavities and aims to provide a comprehensive understanding of flow and heat transfer performance in various kinds of cavities with or without the presence of fins, obstacles, cylinders, and baffles. The study also examines the effects of different forces, such as magnetic force, buoyancy force, and thermophoresis effect on heat transfer in cavities. This study also focuses on different types of fluids, such as air, water, nanofluids, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 277 publications
0
9
0
Order By: Relevance
“…Their findings confirmed that using a multi-blade dynamic modulator enhanced the HT efficiency of the cavity. In 2023, Saha et al [26] presented a configurative systematic review of the research on heat transfer in cavities. The systematic review covered a wide range of topics related to cavity heat transfer, including natural or mixed or forced convection, radiation, and magnetic field effects.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings confirmed that using a multi-blade dynamic modulator enhanced the HT efficiency of the cavity. In 2023, Saha et al [26] presented a configurative systematic review of the research on heat transfer in cavities. The systematic review covered a wide range of topics related to cavity heat transfer, including natural or mixed or forced convection, radiation, and magnetic field effects.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of radiative heat transfer, viscous dissipation, and magnetic force are neglected in this study. The two-dimensional Navier-Stokes equations, which govern the fluid flow and the energy that governs the HT, are presented in a dimensional format, as below 39,50 :…”
Section: Physical Modelmentioning
confidence: 99%
“…The effect of radiative heat transfer, viscous dissipation, and magnetic force are neglected in this study. The two‐dimensional Navier–Stokes equations, which govern the fluid flow and the energy that governs the HT, are presented in a dimensional format, as below 39,50 : ux+vy=0, $\frac{\partial u}{\partial x}+\frac{\partial v}{\partial y}=0,$ ρ)(uux+vuy=px+μ)(2ux2+2uy2, $\rho \left(u\frac{\partial u}{\partial x}+v\frac{\partial u}{\partial y}\right)=-\frac{\partial p}{\partial x}+\mu \left(\frac{{\partial }^{2}u}{\partial {x}^{2}}+\frac{{\partial }^{2}u}{\partial {y}^{2}}\right),$ ρ)(uvx+vvy=py+μ)(2vx2+2vy2+ρgβ(TT0), $\rho \left(u\frac{\partial v}{\partial x}+v\frac{\partial v}{\partial y}\right)=-\frac{\partial p}{\partial y}+\mu \left(\frac{{\partial }^{2}v}{\partial {x}^{2}}+\frac{{\partial }^{2}v}{\partial {y}^{2}}\right)+\rho g\beta (T-{T}_{0}),$ ρCp)(uTx+vTy=α)(2Tx2+2T…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,19] Heat transfer within an enclosure is due to conduction and convection. [20][21][22][23][24] Detailed analysis of natural convection within an enclosure will be investigated over a range of Rayleigh numbers within the laminar flow regime of the NF.…”
Section: Introductionmentioning
confidence: 99%